Assessment of Factors Affecting Quality of Life of Elderly Clients Coveraged Bye Health Centers of Southern of Tehran - Hasan Eftekhar Ardebili; Zohre Sadat Mirsaeidi (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives: The world population is aging rapidly because of rising life expectancy and deacrising fertility rate.with increasing longevity and special aging problems attention and evaluation the quality of life of elderly for health promotion would be significant importance Methods & Materials: this study is a descriptive and analytical study carried out to investigate the quality of life of elderly clients coveraged bye health centers of southern of tehran, in 2010-2011.132 elderly clients were selected by using the cluster randomised sampling from 5health centers. in this study a short form standard questionnaire (sf36)was used for evaluation diverse domains of life quality scores. we also measured some other personal characteristics through demographic questionnaire. data were analyzed with descriptive and analytic statistics by spss software. Results: the mean score of physical domains of quality of life which was 54.42±24.42 and emotional domain of quality of life was 55.19±24.04. mean age was 67.97±6.86. research showed age had meaninful reverse relationship to quality of life (P=0.000, r=-0.4), men had higher quality of life scores than women.education level was directly related to all domains of life quality (P=0/000). married persons and who they lived with childerns or others had the higher quality of life scores than singles (divorced, widow) (P<0.001). and physical activity was directly related to quality of life (P=0.000). but statistically significant differences were not found between the mean score of quality of life and BMI. (physical domain: P=0.59-emotional domain: P=0.127). notsmokers had higher quality of life scores than smokers. (P<0.05). Conclusion: total score of quality of life of elderly was moderate (54.81). therrefore attention and try to improving the quality of life of elderly clients is essential.